Handbook of Metalloproteins 2004
DOI: 10.1002/0470028637.met034
|View full text |Cite
|
Sign up to set email alerts
|

Pitrilysins/Inverzincins

Abstract: Inverzincins are characterized by an inverted zinc‐binding motif (HxxEH) rather than the classical zincin motif (HExxH). Pitrilysin from Escherichia coli is the prototype of one subfamily, which also contains eukaryotic family members such as the insulin‐degrading enzyme (IDE) and the N ‐arginine dibasic convertase (NRDc), both playing important roles in hormone metabolism and cellular regulation. The topology of active site residues s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Recent structural analysis revealed that human IDE consists of two roughly equally sized N- and C-terminal domains (IDE-N and IDE-C)3. IDE-N and IDE-C are homologous to each other and have an αβαβα-roll structure, shared among proteases within the M16 family, which include mitochondrial processing peptidase, pitrilysin, and mitochondrial presequence peptidase5; 6; 7. IDE-N and IDE-C are joined by an extended 28 amino acid loop, and together they form an enclosed chamber to selectively enclose and cleave certain peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Recent structural analysis revealed that human IDE consists of two roughly equally sized N- and C-terminal domains (IDE-N and IDE-C)3. IDE-N and IDE-C are homologous to each other and have an αβαβα-roll structure, shared among proteases within the M16 family, which include mitochondrial processing peptidase, pitrilysin, and mitochondrial presequence peptidase5; 6; 7. IDE-N and IDE-C are joined by an extended 28 amino acid loop, and together they form an enclosed chamber to selectively enclose and cleave certain peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, IDE needs to undergo a significant conformational change from the open state, which can accept substrate, to the closed state for proper substrate recognition and catalysis. The structural comparison of substrate-bound IDE with substrate-free Escherichia coli pitrilysin (PDB accession code 1Q2L) reveals how repositioning between IDE-N and IDE-C can lead to the open state, which allows substrate to access the catalytic cavity 16 ( Fig. 3b and Supplementary Fig.…”
mentioning
confidence: 99%
“…10). Similar to IDE, MPP also uses the exosite for substrate recognition 16,27,28 . The catalytic chamber of MPP stays open, however, whereas IDE has a buried catalytic site in the structure and access to this chamber is kinetically controlled by the closed-open conformational switch.…”
mentioning
confidence: 99%
“…In fact, they act cooperatively to remove the presequences from the precursor proteins. In particular, α-MPP participates in the substrate recognition through many binding sites negatively charged and present in its C-terminal domain and a highly conserved region rich in glycine and histidine residues, ,,, and β-MPP is the catalytic subunit …”
Section: Introductionmentioning
confidence: 99%